Clinical implication of sarcopenia in patients with acute decompensated heart failure: Design and rationale - Bingqing Bai; Dujuan Li; Mingyu Xu; Yingxue Liao; Haofeng Zhou; Fengyao Liu; Wen Li; Huan Ma (ESC Heart Failure, 2025)
Abstract Background Sarcopenia is widely recognized as an age‐related syndrome that involves a progressive loss of skeletal muscle mass and muscle strength. Many studies have shown that sarcopenia is associated with disease severity and exercise intolerance, as well as an independent predictor of mortality in patients with chronic heart failure. However, there is little research on the impact of sarcopenia on patients hospitalized with acute decompensated heart failure (ADHF). Methods This is a prospective, multicentre, observational cohort study. Enrolment of at least 500 participants adults aged over 18 years hospitalized for ADHF is planned, with a minimum of 195 cases each for patients with and without sarcopenia. Each patient is followed up for 6 months, 1 year, 2 years or until the occurrence of endpoint. The primary clinical outcome is all‐cause mortality at 6 months. Other clinical outcomes of interest include cardiovascular mortality, all‐cause hospitalization, heart failure hospitalization and survival time from enrolment to event occurrence. The sympathetic nervous activity, psychosocial factors, quality of life, physical function, and physical activity will be assessed and recorded at baseline. This study will examine the correlation between sarcopenia and prognosis in different subgroups of patients, and explore the additive effect of different comorbidities and sarcopenia on prognosis in patients with ADHF. Conclusions This study will provide important information and evidence on the clinical aspects of sarcopenia in patients with ADHF, potentially contributing to accurate risk stratification and optimal clinical management for patients with ADHF. REGISTRATION: (URL: https://www.clinicaltrials.gov); Unique identifier: NCT06298825.